Solutions to mobilize investment capital in the new rural program in Bu Gia Map district, Binh Phuoc province - Phạm, Mạnh Hùng; Nguyễn, Thị Mỹ Linh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
This article is designed to propose policy implications to help increase the mobilization of investment capital for new rural construction, and to well implement the new rural construction program set out by the Party and State. Primary data was collected by using a questionnaire to directly interview households in the area by simple random sampling method, with a sample size of 45 observations. This study was carried out through two main steps: Preliminary research using qualitative methods through theoretical basis, literature review combined with expert interview techniques and formal research using formal methods. quantitative method. The research shows that the proportion of state budget capital structure invested in the new rural program is quite low compared to the target set out by the National Target Program on new rural construction. After analyzing the advantages and disadvantages in mobilizing investment capital in the new rural program in Bu Gia Map district, the article has proposed four solutions to improve the efficiency of using capital for construction investment. building new rural areas in Bu Gia Map district, Binh Phuoc province in the period of 2022 - 2025.